Gender asymmetry in German phraseology: Linguistic, cultural and psycholinguistic perspectives - Лозицька, Марія; Zubach, Oksana (East European Journal of Psycholinguistics, 2023)
The article is focused on identifying the specifics of gender asymmetry in German phraseology based on psycholinguistic analysis. The aim is to determine the essence of using the internal code of the speaker's intentions while verbalising gender in the target language culture. The study used the method of a controlled word association test. Google Forms were used to analyse the perception peculiarities of the German idioms components that directly or indirectly denote male and/or female gender. The typicality and individuality of responses to the 26 proposed phraseological units with masculine (Mann, Mensch, Drache, Luder) and feminine (Mädchen, Frau, Dame, Weib) components confirmed the asymmetry and unevenness of gender representation in German. The test involved 81 native speakers (56 women and 25 men) aged 14 to 71 residing in Germany and 82 non-native speakers (70 women and 12 men). None of the participants associated themselves with the third gender. Gender asymmetries characterise German phraseology due to the androcentricity of the German language. The associative representation of the male gender in phraseology due to the processes of metonymisation predicts its leading role in the target linguistic culture. Exclamatory and comparative phraseology registers traces of gender asymmetry neutralisation. However, researchers have discovered that phraseological units with a feminine component exclusively serve to denote feminine traits and homosexuality. The feminine component for a man mainly implicates negative connotations, while expressing neutral and positive ones indirectly. Pejorative idioms with a pronounced negative connotation, treating women as sexual objects or as an appendage of a man, deserve attention in the responses. The respondents' responses to phraseological units with neuter or masculine components predominantly denote the female gender through manifested negative connotations. The responses to the component Mädchen, the suffix -chen of which in German actualises the seme of the neuter category, were mainly negative due to the influence of the denotative and signifying meaning of the phraseological unit. The analysis of the zero associations of some phraseological units with women showed the dominant role of men in the target linguistic culture.Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Mariia Lozytska, 0000-0002-0647-3103  maria@vnu.edu.ua